OLEO ESSENCIAL EM ALGUMAS ESPECIES DE EUCALYPTUS - Ming, Lin Chau [UNESP]; Seiko Takemura, O. [UNESP]; Rodrigues Marquesini, N. [UNESP]; Moreira, E. A. [UNESP] (My University, 1995)
In this work we used leaves of four species of Eucalyptus - E. bicostata Maiden, E. deanei Maiden, E. dunnii Maiden and E. viminalis Labill, grown in Colombo, Parana State, Brazil. Preliminary studies were done, in the following sequence: botanic identification, olfactory research, extraction and purification of the essential oil of each species. The physical and chemical tests done were the following: relative density, refractive index, optical rotation, solubility, coagulation point and cineol percentage. The essential oils analysed through gaseous chromatography, presented the following cineol percentage: E. bicostata Maiden - 26.92%, E. deanei Maiden - 70.21%, E. dunnii Maiden - 53.16% and E. viminalis Labill - 23.05%.
Essential oil in some species of Eucalyptus
Keywords: essential oil; botany; drug determination; drug isolation; Eucalyptus; gas chromatography; medicinal plant; phytochemistry